PEMBAHARUAN BATAS USIA ANAK DALAM UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DIKAITKAN DENGAN PERTANGGUNGJAWABAN PIDANA ANAK - Gie Saputra. R, Hartanto An (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The delinquency is an act or acts of violation of norms, both legal norms and social norms committed by children younger ages. Criminal offenses committed by children, was like a criminal act has been committed by an adult even beyond criminal offenses committed by adults.Based on this understanding, the authors formulated two formulation of the problem, namely: First, What is the urgency of renewing the age limit of children in Act No. 11 of 2012 on the Criminal Justice System Children associated with the criminal responsibility of children to children who commit criminal acts. Second, How are ideally age and criminal liability of children in the Criminal Code of children who commit criminal acts.This type of research can be classified in normative law research (legal research) or also called the research literature, because in this study the authors conducted a normative juridical approach under study is library materials or secondary data, which consists of primary legal materials, secondary law, and tertiary legal materials, while the collection of data used in the writing of this study is to use the method of assessment literature or documentary study then analyze the data quantitatively, which is basically the highlighting of the problem and attempt to solve, undertaken with the efforts that many are based on measurements which solves the objects of research in certain elements, then pulled a generalization of the widest possible scope.From the research there are three main issues which can be summarized as follows: First, provide awareness especially to writers and readers in general urgency of renewing the age limit of children in Act No. 11 of 2012 on the Criminal Justice System Children associated with the criminal responsibility of children. Second, to sensitize the general public about the ideal age limit and criminal liability of children in the Criminal Code of children who become perpetrators of criminal acts. Third, contribute ideas and tools to encourage fellow students to continue further research on the renewal of an age limit of children in Act No. 11 of 2012 on the Criminal Justice System Children on children who commit criminal acts.Keyword: Updates - Limit - Age - Children - Responsibility - Criminal